Comparative Analysis of Types of Liability and Punishments for the Falcification of Mediсines in Countries of European Union - Tulegenova Аigerim (Journal of Global Pharma Technology, 2018)
The article presents the results of an analysis of modern approaches in determining the types of responsibilities and penalties for falsification of medicines in the EU countries. It is determined that, process of recognition and implementation of norms and requirements of The Medicrime Convention in the states that are members to the Council of Europe continues and dynamically develops. The changes, which were adopted after the signature by the EU countries of The Medicrime Convention in 2011, are analyzed. Determined, that out of all liabilities which exist in jurisprudence in regards to the issue of falsification of medicines, the criminal, administrative and civil liabilities are applied. Current practice exists in all 28 EU states. It was found that in most of the EU countries (10 countries) relatively soft criminal sanctions (from 1 to 3 years of imprisonment) dominate for the falsification of medicines. In addition, there is no consolidated position as to what kinds of offenses for falsification in the pharmaceutical market criminal sanctions should be applied. It is found that the maximum values of penalties for falsification of medicines in the EU countries varies in a wide range of indicators (from 4,3 thousand euro to 1 million euros). Relatively soft criminal sanctions in most EU countries and a wide range of fines for drug fraud contribute to the migration of organized crime in the pharmaceutical business. However, it should be noted that the positive experience of struggling against counterfeiting in the EU has great practical significance for countries with low income and health systems, which are in the stage of reforming.Keywords: Falsification of medicines, Punishment for falsification of medicines, Types of liability for falsification of medicines, The Medicrime Convention.